2002
DOI: 10.1007/s00438-001-0615-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel MADS-box gene subfamily with a sister-group relationship to class B floral homeotic genes

Abstract: Class B floral homeotic genes specify the identity of petals and stamens during the development of angiosperm flowers. Recently, putative orthologs of these genes have been identified in different gymnosperms. Together, these genes constitute a clade, termed B genes. Here we report that diverse seed plants also contain members of a hitherto unknown sister clade of the B genes, termed B(sister) (B(s)) genes. We have isolated members of the B(s) clade from the gymnosperm Gnetum gnemon, the monocotyledonous angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 33 publications
8
94
0
Order By: Relevance
“…Importantly, orthologous relationships between floral organ identity genes from angiosperms and any of the MIKC C genes from S. moellendorffii were not detected. Previous analyses found orthologs of some floral organ identity genes in gymnosperms, but had suggested that these genes are absent from non-seed plants such as mosses and ferns (e.g., Muenster et al, 1997; Hasebe et al, 1998; Mouradov et al, 1999; Sundstrom et al, 1999; Krogan and Ashton, 2000; Theißen et al, 2000, 2001; Becker et al, 2002; Henschel et al, 2002; Svensson and Engstrom, 2002; Becker and Theißen, 2003). However, because whole-genome data were lacking, the possibility that those orthologs in non-seed plants simply escaped detection had not been ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, orthologous relationships between floral organ identity genes from angiosperms and any of the MIKC C genes from S. moellendorffii were not detected. Previous analyses found orthologs of some floral organ identity genes in gymnosperms, but had suggested that these genes are absent from non-seed plants such as mosses and ferns (e.g., Muenster et al, 1997; Hasebe et al, 1998; Mouradov et al, 1999; Sundstrom et al, 1999; Krogan and Ashton, 2000; Theißen et al, 2000, 2001; Becker et al, 2002; Henschel et al, 2002; Svensson and Engstrom, 2002; Becker and Theißen, 2003). However, because whole-genome data were lacking, the possibility that those orthologs in non-seed plants simply escaped detection had not been ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…MIKC* genes are not well characterized but several appear to play important roles in the development of the male gametophyte (pollen) in angiosperms (Kofuji et al, 2003; Verelst et al, 2007a,b; Adamczyk and Fernandez, 2009; Zobell et al, 2010). In contrast, angiosperm MIKC C genes have been studied in depth since many of them are key regulators of flowering time, floral organ identity, and fruit development (Schwarz-Sommer et al, 1990; Yanofsky et al, 1990; Huijser et al, 1992; Mandel et al, 1992; Pnueli et al, 1994; Michaels and Amasino, 1999; Ambrose et al, 2000; Lee et al, 2000; Honma and Goto, 2001; Becker et al, 2002; Becker and Theißen, 2003; Ferrario et al, 2003; Ditta et al, 2004; Pabón-Mora et al, 2012). Although gymnosperms possess orthologs representing most of the clades of MIKC C floral developmental genes, phylogenetic analyses show that the genes identified from ferns, lycophytes, and mosses comprise other MIKC C clades (Muenster et al, 1997; Hasebe et al, 1998; Mouradov et al, 1999; Sundstrom et al, 1999; Becker et al, 2000; Krogan and Ashton, 2000; Henschel et al, 2002; Svensson and Engstrom, 2002; Tanabe et al, 2003, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, functional analysis of a mutant revealed that OsMADS13 controls ovule identity in rice (Dreni et al 2007). In addition, genes closely related to class B MADS-box genes have been identified by phylogenetic studies, and are referred to as B sister genes (Becker et al 2002). ARABID-OPSIS BSISTER (ABS) from Arabidopsis and FBP24 from Petunia are the members of the B sister subfamily and are necessary for determining the identity of the endothelial layer within the inner integument of the ovule (Nesi et al 2002;de Folter et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago, the sister clade of class B genes ( DEF / GLO -like genes, also known as AP3 / PI -like genes), termed B sister genes, was identified in both angiosperms and gymnosperms [6]. Protein sequence alignments with other MADS-domain proteins indicated that compared to other MIKC-type proteins, the proteins encoded by B sister genes share a shorter I domain, a sub-terminal PI Motif-derived sequence and, in some cases, also a PaleoAP3 Motif in the C-terminal region with the AP3/PI-like proteins of gymnosperms and angiosperms [6].…”
Section: Introductionmentioning
confidence: 99%